Enhancing Students’ Critical Thinking Skills: The Impact of Project-Based and Task-Based Learning Across Motivation Levels - Haviz Kurniawan; Bunyamin Maftuh; Babang Robandi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Enhancing elementary students’ critical thinking skills is a key educational objective. Instructional approaches such as Project-Based Learning (PjBL) and Task-Based Learning (TBL) are widely used, with their effectiveness potentially influenced by students’ learning motivation.This quantitative study employed a quasi-experimental approach using a one-group pretest–posttest and a 2×3 factorial design without randomization. The sample consisted of 50 sixth-grade students from an elementary school in Bandung, Indonesia. Data were collected באמצעות critical thinking tests and learning motivation questionnaires. Statistical analyses were conducted to examine the effects of instructional methods and motivation levels.Students taught PjBL demonstrated higher average gains in critical thinking skills compared to those taught TBL. Both PjBL and TBL significantly improved students’ critical thinking abilities. Additionally, learning motivation had a positive and significant effect on critical thinking outcomes across both instructional methods. Interaction effects indicated that the impact of each method varied depending on students’ motivation levels.The findings suggest that while both PjBL and TBL are effective in fostering critical thinking, PjBL yields superior outcomes. Learning motivation plays a crucial role in maximizing the effectiveness of these instructional approaches. Therefore, integrating motivational strategies with appropriate pedagogical methods is essential to optimize students’ critical thinking development.